Anticorpos IgA, IgE e IgG4 específicos a Dermatophagoides pteronyssinus e aos seus alérgenos principais, Der p 1 e Der p 2, em amostras de soro e saliva de crianças e adolescentes alérgicos e não-alérgicos - Miranda, Diego Oliveira (2009)
Allergic rhinitis (AR) is a global public health problem and it is gaining importance due to the rapid increase in its prevalence worldwide. House dust mites as Dermatophagoides spp. are the major sources of allergen sensitization in genetically predisposed subjects. This study aimed to evaluate serum and salivary IgA, IgE and IgG4 levels to Dermatophagoides pteronyssinus (Dpt) and its major allergens (Der p 1 and Der p 2) in allergic and non-allergic children and teenager. A total of 86 subjects were studied, from which 72 had AR and positive skin test to Dpt extract, and 14 were non-allergic subjects, with negative skin test to aeroallergens. Paired serum and saliva samples were collected from all subjects and analyzed by immunoenzymatic assays. Levels of serum IgE and serum or salivary IgG4 antibodies to Dpt, Der p 1, and Der p 2 were higher in allergic than non-allergic children and teenager (p < 0.05). In contrast, levels of serum and salivary IgA antibodies to all allergens were higher in non-allergic than allergic children and teenager (p < 0.05). It was noted that the ratio serum IgG4/IgE was lesser than 1.0 to all allergens and significantly lower in allergic than non-allergic children and teenager. It can be concluded that allergic children and teenager have high levels of serum IgE and IgG4 serum and salivary allergen-specific and low levels of serum and salivary IgA allergen-specific to Dpt, Der p 1 and Der p 2. Specific IgG4 antibodies are present in the serum and saliva from allergic children and teenager along with specific serum IgE, but IgE predominates in the serum of allergic children and teenager whereas IgG4 prevails in the serum of non-allergic children. Specific IgA appears to act as natural protective antibody since it predominates in the serum and saliva from non-allergic children and teenager.